Gene-targeted-metagenomics reveals extensive diversity of aromatic dioxygenase genes in the environment - Iwai, Shoko (2009)
Understanding the relationship between gene diversity and function for important environmental processes are major ecological research goals. We applied gene-targeted-metagenomics and pyrosequencing to aromatic dioxygenase genes to obtain greater sequence depth than possible by other methods. A PCR primer set designed to target a 524 bp region that confers substrate specificity of biphenyl dioxygenases yielded 2000 and 604 sequences from 5′ and 3′ ends of the PCR products, respectively, that passed our validity criteria. Sequence alignment showed three known conserved residues as well as another seven conserved residues not previously reported. Ninety-five and 41% of the valid sequences were assigned to 22 and 3 novel clusters in that they did not include any previously reported sequences at 0.6 distance by Complete Linkage Clustering for the sequenced regions. The greater diversity revealed by this gene-targeted approach provides deeper insights into genes potentially important in environmental processes to better understand their ecology, functional differences and evolutionary origins. We also provide criteria for primer design for this approach as well as guidance for data processing of diverse functional genes since gene databases for most genes of environmental relevance are limited.